Frontiers : Gyrated dice achieve perfect packing. (9th February 2018) - Skuse, Benjamin
Abstract: A new and rapid way to pack identical cubes in a dense configuration has been discovered by physicists in Spain and Mexico led by Diego Maza of the Universidad de Navarra.